Effect of Dental Restorative Material Type and Shade on Characteristics of Two-Layer Dental Composite Systems - Karimzadeh, A.; Ayatollahi, M.R.; Bushroa, A.R. (Brazilian Society of Mechanical Sciences and Engineering, 2016)
The purpose of this study was to investigate the effects of shade and material type and shape in dental polymer composites on the hardness and shrinkage stress of bulk and two-layered restoration systems. For this purpose, some bulk and layered specimens from three different shades of dental materials were prepared and light-cured. The experiments were carried out on three types of materials: conventional restorative composite, nanohybrid composite and nanocomposite. Micro-indentation experiment was performed on the bulk and also on each layer of layered restoration specimens using a Vicker’s indenter. The interface between the two layers was studied by scanning electron microscopy (SEM). The results revealed significant differences between the values of hardness for different shades in the conventional composite and also in the nanohybrid composite. However, no statistically significant difference was observed between the hardness values for different shades in the nanocomposite samples. The layered restoration specimens of different restorative materials exhibited lower hardness values with respect to their bulk specimens. The reduction in the hardness value of the layered conventional composite samples was higher than those of the nanocomposite and nanohybrid composite specimens indicating more shrinkage stresses generated in the conventional composite restorations. According to the SEM images, a gap was observed between the two layers in the layered restorations.